Let's Talk About Sex: Improving the Adoption of Pre-exposure Prophylaxis by Internal Medicine Resident Physicians in New Orleans. (4th October 2017) - Bartram, Logan; Chiosi, John; Varley, Cara; Halperin, Jason
Abstract: Background: An estimated 1.2 million adults in the US have an indication for pre-exposure prophylaxis (PrEP). However, the practice of prescribing PrEP by primary care providers (PCPs) continues to be low and ranges from 17–35% in recent studies. PCPs are best positioned to provide PrEP as a prevention tool before referral to an HIV specialist. New Orleans has the third highest incidence of HIV in the US; therefore, PCPs need to be adequately trained in providing PrEP. We implemented a resident-led quality improvement project to evaluate knowledge of PrEP and implement a training program to increase adoption of PrEP in internal medicine resident clinics. Methods: An anonymous, online survey to assess PrEP knowledge and practices was conducted among resident and attending physicians in an internal medicine training program in New Orleans, Louisiana in 2017. We used SAS 9.4 for descriptive analyses and to evaluate variables associated with higher survey scores. Results: We received 111 responses out of 153 (72.5%) physicians invited to participate, 100/140 (71.4%) of resident physicians and 11/13 (84.6%) of attending physicians. 93.6% of respondents had heard of PrEP and 75.2% were aware of published guidelines. Few had discussed (41.4%) or prescribed (14.4%) PrEP with at least 1 patient and 62.5% of those prescribing had done so only within an infectious disease clinic rotation (Figure 1). 50 (45.9%) respondents reported only taking a sexual history when in relation to a patient's chief complaint and 9 (8.3%) rarely asked about sexual history. Being unsure of patient eligibility, medication management, monitoring requirements and limitations in clinic were cited as barriers to adoption of PrEP (Figure 2). Respondents scored an average of 7.9 out of a possible 13 points (61%) regarding knowledge about PrEP based on CDC prescribing guidelines. There was a significant association between reported familiarity with PrEP (P < 0.01) and survey score. Conclusion: Few internal medicine resident physicians who practice in New Orleans, a high-risk community for HIV, have experience prescribing PrEP, and there are opportunities to address gaps in knowledge that are the reported barriers to prescribing. Disclosures: J. Halperin, Gilead Sciences: Investigator, Research grant